Prospective multicenter study of the breakable babystent for treatment of aortic coarctation in newborns and infants. Issue 5 (16th February 2022) - Stiller, Brigitte; Zartner, Peter; Dähnert, Ingo; Haas, Nikolaus A.; Schubert, Stephan; Kanaan, Majed; Berger, Felix; Ewert, Peter; Schmoor, Claudia; Grohmann, Jochen
Abstract: To assess the efficacy and safety of a breakable BabyStent to treat complex aortic coarctation (CoA) in early childhood. Although recommended in several guidelines, there is no approved aortic stent for young infants, because of the dilemma between two mandatory requirements: expandable up to adult size on the one hand, and small enough to fit through a baby's femoral artery on the other. Prospective interventional, multi‐center clinical trial with the breakable Osypka BabyStent® (OBS). The OBS is a low‐profile, 15‐mm long cobalt‐chromium stent, pre‐mounted on a 6 mm balloon and inserted via a 4 Fr sheath. After implantation, its diameter is adjustable from 6 to 12 mm by balloon dilation. Further dilation opens predefined joints enabling unrestricted growth. Nineteen patients (9 male), median age 112 days (range: 7–539), median body weight 5.6 kg (range: 2.4–8.4) were deemed high risk and underwent stent implantation. Of those, 74% suffered from re‐CoA following surgery, 53% had additional cardiac and 21% noncardiac malformations. Our primary combined endpoint was fulfilled: All stents were implanted in the desired region, and a >50% intrastenotic diameter‐extension was achieved in 15 patients (78.9%, 80% confidence interval [62.2; 90.5], 95% confidence interval [54.4; 93.9]). Secondary endpoint confirmed that the OBS fits the baby's femoral vessel diameter. All children survived the procedure and 12‐month follow‐up. This stent enables percutaneous stenting of complex aortic coarctation to treat high‐risk newborns and infants.